Analyzing the job search challenges of persons with disabilities in Manila : ways in reducing social stigma and increasing employment opportunities. - Cabungan, Hannah Joy C. Najera, Cassandra G. Reyes, Anri Sharylle Rocio, Kathleen Mae B. Rojo, Bev Marlem T. Trinidad, Maxine Ice C. 4 0 16; 5
ABSTRACT With an emphasis on the interaction between social stigma and employment obstacles this study examines the diJiculties Persons with Disabilities in Manila face when looking for work. Many Persons with Disabilities still encounter major barriers that restrict their access to fulfilling employment, even in laws that are in place to encourage their inclusion in the workforce. Important findings show that widespread social stigma, which comes from false beliefs regarding the skills of Persons with Disabilities, has a big impact on employment processes and company attitudes. A lot of businesses have doubts about Persons with Disabilities' dependability and productivity, which frequently results in discriminatory hiring practices. The study also identifies systemic problems like a lack of accessible employment opportunities, poor PWD-specific training programs, and a lack of assistance from governmental and non-governmental groups.
Business Research : (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila , 2024.
Keywords: 2 -- 0; 6; 20; 20; 2